The effects of self-esteem and locus of control on self reported personal reputation - Erkmen, Turhan; Esen, Emel (GURUKUL KANGRI UNIV, FAC MANAGEMENT STUDIES, 2019)
Purpose-The purpose of this study is to examine the effect of such personality traits as self-esteem and internal locus of control on personal reputation of manager trainees. This study may help to draw attention to the management trainees who are potential and probably future managers of companies in various industries in order to clarify how the relationship between individual variables (eg. self-esteem and internal locus of control) can influence their personal reputation. Design/methodology/approach - An empirical study was conducted with 196 management trainees from different industries of BIST (Borsa Istanbul) 100 companies in Istanbul, Turkey. The questionnaire was constructed to assess the main variables of the study (self-esteem, internal locus of control and personal reputation) and demographic characteristics. Findings - Confirmatory factory analysis (CFA) were performed for each scale. The findings of multiple regression analysis show that both self-esteem and internal locus of control have impact on personal reputation. Internals have higher personal reputation than people who have high self-esteem. Research limitations/implications - This study was conducted among management trainees. Therefore, the results of the study cannot be generalized to other groups. Practical implications - This study may draw business people's attention to the importance of developing such characteristics as a challenge for business success in such a rapidly changing, competitive global business environment. Originality/value - This study is valuable in order to analyze the reputation at individual level while most studies in the literature examine reputation at organization level. Particularly, when a manager's personal reputation's influence on an organization's reputation is assumed, this study may provide some beneficial findings for future studies to explain company reputation from an individual aspect.
Keywords: Personal reputation; Self-esteem; Internal locus of control; Management trainees; POLITICAL SKILL; LEADER REPUTATION; JOB-SATISFACTION; PERFORMANCE; ORGANIZATIONS; ANTECEDENTS; DELINQUENT; ROLES; Business & Economics